Transformation to Law Enforcement Gambling Crimes in Indonesia - christine susanti (Faculty of Law, Universitas Pekalongan, 2023)
Gambling is nothing new, since a long time ago this crime has existed. Initially, gambling was done with conventional methods, but along with the development of technology, gambling has also experienced developments and now it has entered the digital space. The rise of online gambling has made the government declare Indonesia's condition of gambling emergency. Minister of Communication and Information (Menkominfo) Budi Arie even stated that he intends to fight gambling within a week. Gambling was originally a social problem, but later it has developed into a legal problem that demands comprehensive and continuous regulation and law enforcement. This research will discuss how law enforcement practices in Indonesia in eradicating gambling and how Indonesian law solves the problem comprehensively. The research method used is a normative research method or commonly called literature research by examining library materials or secondary data with a case approach. Several relevant legislation products will be used as legal bases in this research, such as the Criminal Code (KUHP) and Law Number 19 of 2016 concerning Electronic Information and Transactions. This research wants to provide input to the government in supporting the law enforcement process against gambling and also help increase the level of public legal awareness of gambling crimes both online and conventional.